DESIGN OF MULTI-POWERED SOLAR BOAT - Yogesh Patil; Amol Mali; Salim Shaikh; Avinash Madane; Digambar Kashid; Sunilkumar Bandgar (International Journal of Innovations in Engineering Research and Technology, 2022)
Backwater Tourism is the prime attraction. Diesel engine driven boats are conventionally employed for water transport. The fumes emitted into the water results in water pollution. Incorporation of renewable energy in an electric boat can promote sustainable tourism. The goal of this paper is to design a Multi-Powered Boat for tourist transportation along the coast, rivers, and lakes. Our plan is to develop project guidelines for the construction of a zero-impact boat. Switched Reluctance Motor (SRM) due to rugged construction as well as high performance can be used in electric boats. Solar energy available in plenty can act as the driving source for this motor. Battery bank can supplement the surplus power required depending on the load requirement. So, this hybrid boat is not going to create any environmental pollution objects. As, we are using solar energy which is freely available in nature.